Optimization of a Gas Chromatography–Mass Spectrometry (GCMS) Method for Detecting 28 Allergens in Various Personal Care Products - Adnan S. AL-Mussallam; Abdullah T. Bawazir; Rawan S. Alshathri; Omniyah Alharthi; Fahad S. Aldawsari (Cosmetics, 2023)
Fragrances are among the most common ingredients in cosmetics products. Importantly, exposure to fragrances on a daily basis might pose a health risk, leading to serious effects, such as contact dermatitis or contact eczema. Annex III of the European Union Directive on Cosmetic Products and Gulf Cooperation Council standardization organization (GSO) introduced restrictions for 26 allergens, with their concentrations exceeding 0.001% and 0.01% in leave-on products and rinse-off products, respectively. In the current study, we aimed to expand the scope of the analytical method (EN16274, 2012) to include a broader range of matrices. The optimized method was validated by examining a statistical approach, including selectivity, linearity, accuracy, precision, and measurement of uncertainty. Successfully, the validated data demonstrated acceptable limits according to validation protocols, with linearity showing satisfactory regression of r > 0.995. During method performance assessment, samples were extracted using ultrasound-assisted extraction to extract allergens that yielded relatively high recoveries. Studies on matrices spiked with allergens at different levels showed insignificant bias as an average of 0.07 µg/g. Method performance was assessed by analyzing 140 cosmetics samples, including perfumes, deodorants, aftershave, baby wet wipes, shampoos, lotions, and lip care products. The new optimized analytical method is believed to be a valuable analytical tool to be used in surveillance studies covering a wide range of cosmetic matrices.